PEMANFAATAN AUGMENTED REALITY BERBASIS OBJEK 3D UNTUK PENGENALAN ORGAN TUBUH MANUSIA - Subhan Hartanto; Sarwo Edi Wibowo; Almasari Aksenta (Smart Education, 2026)
The development of digital technology encourages innovation in learning media that is more interactive and easier for students to understand. One technology that can be used is Augmented Reality or AR, which combines three-dimensional virtual objects with the real environment in real time. This study aimed to design and implement an Augmented Reality-based learning media for introducing human body organs. The development method used was the Luther-Sutopo version of the Multimedia Development Life Cycle or MDLC, consisting of concept, design, material collecting, assembly, testing, and distribution stages. The object used in this study was a three-dimensional model of human anatomy equipped with annotations on several organs, such as the liver, heart, and gut. The implementation results showed that AR media could display human anatomy objects virtually through marker scanning using a mobile device. This media allowed users to observe the shape, position, and parts of human organs more clearly and interactively. Therefore, Augmented Reality-based learning media can be an innovative alternative to help improve students’ understanding and learning interest in human body organ materials.